Analisis Kointegrasi Antara Saham Syariah Dan Tingkat Suku Bunga - Hijrasil; Zandy Pratama Zain (Journal of Islamic Economics and Finance, 2024)
The development of Islamic economics with the application of sharia principles in economic activities is starting to be practiced in the field of sharia finance. This started with the establishment of sharia banking, then followed by the emergence of the sharia capital market as an investment tool to attract profits and seek capital. The Jakarta Islamic Index (JII) as the antithesis of the conventional capital market has challenges when carrying out investments using sharia principles, this is because securities in the form of shares are greatly influenced by macroeconomic aspects such as interest rates. So sharia share prices are very sensitive to the dynamics of interest rates. This research seeks to see the extent of the influence of interest rates on sharia sham prices at JII. The method used is VECM analysis to see long-term effects. The results of this research found that the interest rate variable did not significantly influence sharia stock prices in the long term, however the results of the VECM analysis found that there was a negative relationship, meaning that there was still an influence, although not significant. So sharia share prices can still be affected by changes in conventional interest rates.